2019
DOI: 10.1017/jfm.2019.490
|View full text |Cite
|
Sign up to set email alerts
|

Swimming mediated by ciliary beating: comparison with a squirmer model

Abstract: The squirmer model of Lighthill and Blake has been widely used to analyse swimming ciliates. However, real ciliates are covered by hair-like organelles, called cilia; the differences between the squirmer model and real ciliates remain unclear. Here, we developed a ciliate model incorporating the distinct ciliary apparatus, and analysed motion using a boundary element–slender-body coupling method. This methodology allows us to accurately calculate hydrodynamic interactions between cilia and the cell body under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 33 publications
3
52
2
Order By: Relevance
“…We further remark that comparisons of power and efficiency for swimmers having different gaits (i.e. different values of and ) should be undertaken with caution given recent results suggesting that the squirmer model underestimates the true power expenditure of swimming microorganisms (Ito, Omori & Ishikawa 2019).
Figure 12.Normalized hydrodynamic power and efficiency as a function of Wi and degree of swirl, , for a neutral squirmer ().
…”
Section: Resultsmentioning
confidence: 89%
“…We further remark that comparisons of power and efficiency for swimmers having different gaits (i.e. different values of and ) should be undertaken with caution given recent results suggesting that the squirmer model underestimates the true power expenditure of swimming microorganisms (Ito, Omori & Ishikawa 2019).
Figure 12.Normalized hydrodynamic power and efficiency as a function of Wi and degree of swirl, , for a neutral squirmer ().
…”
Section: Resultsmentioning
confidence: 89%
“…In summary, we utilize the spherical squirmer model for viscoelastic ambient fluids, namely (2.1)–(2.3) with . We also mention here that the suitability of the steady-state squirmer model for the study of real micro-swimmers in biological Newtonian systems has been investigated by Ito, Omori & Takuji (2019). These authors concluded that the steady squirmer model can predict very well the swimming speed of the body but drastically underestimates the power consumption, i.e.…”
Section: The Squirmer Model In Viscoelastic Fluidsmentioning
confidence: 99%
“…Vilfan (2012) optimized the steady slip velocity and the shape at the same time, with constraints on its volume and maximum curvature. The work considered power loss not only outside but also inside the squirmer surface, which could be an order of magnitude higher than the outside power loss alone (Keller & Wu 1977;Ito et al 2019). However, it assumed that the tangential force on the squirmer surface is linear to its local slip velocity, which is not always the case for microswimmers.…”
Section: Introductionmentioning
confidence: 99%